The expectations of generation Z regarding the university educational act in Romania: optimizing the didactic process by providing feedback - Bratu, Mihaela Laura; Cioca, Lucian-Ionel; Nerisanu, Raluca Andreea; Rotaru, Mihaela; Plesa, Roxana (Frontiers in Psychology, 2023)
At the level of the university education system, the evaluation and providing of two-way teacher-student feedback are tools within the control function of educational management. Feedback can be defined as the process that takes place in the context of teacher-student interaction during university courses, at individual and group level, for the development and achievement of the performance of the two actors involved, through evaluation, appreciation, support, perception, and teaching. The research aims to develop an innovative feedback tool for the higher education engineering sector to support the improvement of learning outcomes-oriented curricula and teaching activities to better meet the learning needs of Gen Z students, while being relevant to the labor market and for society in general. The research had a number of subjects of 246 students (67,5% feminine, 32,5% masculine) and 7 teachers, to whom two feedback instruments were applied (SKS instrument and standard instrument of Lucian Blaga University of Sibiu). After testing the four hypotheses, was observed that the feedback provided by Gen Z is on four areas of competence: psychological, pedagogical, education management and general impression. Each field includes a set of professional and transversal competencies. SKS (stop, keep, start) evaluation form is more trustable in evaluating different disciplines than the standard evaluation form, by providing more homogenous type of feedbacks for each discipline or teacher.